INTEGRATING QUR’ANIC VALUES IN EARLY CHILDHOOD PLAY: A LIVING QUR’AN APPROACH - Pujiniarti, Yayu Bondan (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
BackgroundL Habituating life with the Quran from an early age is expected to help children understand, integrate, and accept Quranic values ​​as part of their personal experience. Purpose: This paper discusses the application of the conceptLiving Qur’anin the world of early childhood play as an effort to integrate Quranic values ​​contextually without losing the substance of its teachings. Method: This research uses a qualitative approach with a literature study combined with conceptual analysis of theory. Living Qur’an, early childhood developmental psychology, and play-based Islamic education. Result: The study found that play is an effective method for internalizing Quranic values ​​in young children. Activities such as religious songs, educational games, and interactive stories serve as media that can provide both enjoyable and meaningful learning experiences. Conclusion: Draft Living Qur’anIn this context, it emphasizes the development of children's abilities to enjoy and experience religious experiences naturally according to their developmental stage. Thus, play-based Islamic education is based onLiving Qur’ancan be a holistic education model that integrates cognitive, affective, and spiritual dimensions in the early childhood learning process.